Paintings that evoke mystery - Christensen, Scott Ervin, author; Dietemann, David L., advisor; Yust, Dave, 1939-, committee member (Colorado State University. Libraries, 1986)
My paintings are primarily personal, and they retain significant privacy. In turn, the paintings evoke mystery -- a visual riddle with clues represented by compositional imagery. This-mystery is directly related to basic human experience, and it is my intention that it be symbolic, metaphorical, and metaphysical in content. A meaningful experience is offered through my paintings relative to the viewer's desire to explore these intriguing manifestations.
Keywords: Metaphysical school (Art movement); Painting, American -- 20th century